2016
DOI: 10.3906/vet-1505-17
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone concentration in milk and blood serum and reproductiveefficiency of cows after Ovsynch treatment

Abstract: An experiment was conducted to investigate the effects of hormonal synchronization of ovulation on progesterone concentrations in milk and blood serum and on reproductive performance. Sixty Holstein-Friesian cows averaging 8000 L over 305 days of lactation were divided into 2 groups of 30 animals. One-factor ANOVA and a t-test of progesterone concentrations in venous serum and milk revealed that the lowest concentrations of progesterone in milk (Ovsynch 5.8 ± 1.0 ng/mL; control 4.5 ± 0.6 ng/mL) and blood serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The blood serum P4 concentrations found by us are lower than the level found in Holstein animals stimulated with hCG (Stevenson et al, 2012) but are comparable to concentrations detected in Holstein-Friesian dairy cows subjected to Ovsynch treatment (Vuković et al, 2016). Stevenson and Pulley (2012) reported that treatment with hCG (1000 IU) seven days after AI induces new luteal structures in about 70% of the treated animals and increases blood P4 level.…”
Section: Discussionsupporting
confidence: 73%
“…The blood serum P4 concentrations found by us are lower than the level found in Holstein animals stimulated with hCG (Stevenson et al, 2012) but are comparable to concentrations detected in Holstein-Friesian dairy cows subjected to Ovsynch treatment (Vuković et al, 2016). Stevenson and Pulley (2012) reported that treatment with hCG (1000 IU) seven days after AI induces new luteal structures in about 70% of the treated animals and increases blood P4 level.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, the progesterone profiles appear in the lutheal phase of the estrus cycle. This is consistent with the early report of the higher progesterone concentration in blood serum during the late lutheal phase 3.6 ± 1.1 ng/ml of ovsynch protocol [37] and 1.59 ng/ml [38], [39]. Moreover, the progesterone concentration in blood is higher in the middle of the lutheal phase as compared to the earlier and late luteal phase [40].…”
Section: The Progesterone Concentration Of Local Pesisir Cattle Insupporting
confidence: 92%
“…The similar result reported that the treatment protocol of synchronization programme, 100 percent cows expressed estrus but the intensity varied from prominent, moderate and weak estrus sign [36]. Furthermore, weak estrus behaviour was assumed to be the cause of the decline in breeding efficiency in cattle, and vaginal temperature measurement might be effective for detecting estrus regardless of estrus behaviour [37].…”
Section: Clinical Sign Of Estrus Of Local Pesisir Selatan Cowmentioning
confidence: 57%
“…This also shows that they were in the same stage of the estrus cycle. In addition, the hormone levels in the other blood samples collected from G1 were compatible with the measured hormone levels with applications similar synchronization protocols in a different study [46] . On the other hand, progesterone levels measured during ovsynch were found to be different from our findings in another study.…”
Section: Discussionmentioning
confidence: 70%